Relationship between Self-Efficacy, Emotional Intelligence, and Parental Social Support with Learning Motivation of University Students in Distance Learning during the Covid-19 Pandemic - Iin Andriani; Lisnawati Ruhaena; Nanik Prihartanti (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2022)
Distance learning has an impact on decreasing university students’ motivation to learn. Meanwhile, learning motivation is fundamental in the distance learning process. Learning motivation correlates with internal factors such as self-efficacy and emotional intelligence and external factors such as parental social support. This study aimed to find alternative factors that support learning motivation and examine the relationship between self-efficacy, emotional intelligence, and parental social support with learning motivation in university students carrying out distance learning during the COVID-9 pandemic. The study used quantitative research with the correlational research type involving undergraduate students at the Muhammadiyah University of Surakarta with a total of 408 students. The Academic Motivation Scale-Short version (AMS) was used to measure learning motivation, the General Self-Efficacy Scale (GSES) was used to measure self-efficacy, the Trait Emotional Intelligence Questionnaire-Short Form (TEIQUE-SF) was used to measure emotional intelligence, and the parental social support scale compiled by Fitrotin was used to measure parental social support. Data were analyzed using multiple linear regression tests. The results of the study found that self-efficacy, emotional intelligence, and parental social support had a relationship with learning motivation. This was indicated by the positive value of Beta=27.284, p-value of 0.000 (p <0.005), the regression (F value) of 36.569, the correlation (R)= 0.467, and the effective contribution to learning motivation of 21.8%. Programs to increase self-efficacy, emotional intelligence, and parental social support are important to increase motivation.